Determinants of Entrepreneurial Intent: A Meta–Analytic Test and Integration of Competing Models. (March 2014) - Schlaegel, Christopher; Koenig, Michael
Increasing interest in the development of entrepreneurial intentions has elevated the importance of theories that predict and explain individuals' propensity to start a firm. The purpose of this study is to meta–analytically test and integrate the theory of planned behavior and the entrepreneurial event model. We summarize the findings of 98 studies (123 samples, n = 114, 007) and utilize meta–analytic structural equation modeling to examine the empirical fit of the competing theories and the integrated model. Our results demonstrate support for the competing theories and indicate the moderating role of contextual boundary conditions in the development of entrepreneurial intent. Furthermore, our findings suggest that the integrated model provides additional explanatory power and a fuller understanding of the process through which entrepreneurial intent develops.